Analisis Kesalahan Berbahasa dalam Menulis Teks Pidato Bahasa Arab Siswi Kelas 2 Pondok Modern Arrisalah, Slahung Ponorogo - Miftahul Azizah; Istiqomah; Lisma Meilia Wijayanti (Journal of Conflict and Social Class (JCSC), 2024)
This qualitative study analyzes language errors in Arabic speech texts written by second-grade female students at Pondok Modern Arrisalah, Slahung, Ponorogo. The research aims to provide a detailed understanding of error patterns within the context of Arabic language learning. It is descriptive in nature, focusing on grammar, vocabulary, and sentence structure errors in the students' speech texts. Data were collected through a documentation study of prepared Arabic speech texts, and common error patterns were identified through language error analysis. The research employs a content analysis approach for a meticulous examination of language errors. The study refers to relevant concept models, including previous research on error analysis in Arabic language learning. In the context of Asset-Based Community Development (ABCD), the research considers the positive aspects and resources of the students and their learning environment to support the development of Arabic writing skills for second-grade female students. The findings aim to guide the development of effective learning strategies for improving Arabic speech writing skills.